Frequency and risk factors for naturally occurring Cushing's syndrome in dogs attending UK primary‐care practices. (8th December 2021) - Schofield, I.; Brodbelt, D. C.; Niessen, S. J. M.; Church, D. B.; Geddes, R. F.; O'Neill, D. G.
Abstract : Objectives: To estimate the frequency and risk factors for Cushing's syndrome in dogs under UK primary veterinary care. Materials and Methods: Dogs with Cushing's syndrome were identified by searching electronic patient records of primary‐care veterinary practices. Pre‐existing and incident cases of Cushing's syndrome during 2016 were included to estimate the 1‐year period prevalence. Incident cases were used to estimate the annual incidence and to identify demographic risk factors for the diagnosis of Cushing's syndrome in dogs, through multivariable logistic regression. Results: Analysis included 970 pre‐existing and 557 incident cases of Cushing's syndrome from a population of 905, 544 dogs. The estimated 1‐year period prevalence for Cushing's syndrome in dogs under veterinary care was 0.17% (95% confidence interval 0.16 to 0.18) and incidence was 0.06% (95% confidence interval 0.05 to 0.07). In multivariable logistic regression modelling, the Bichon frise (odds ratio=6.17, 95% confidence interval 4.22 to 9.00), Border terrier (5.40, 95% confidence interval 3.66 to 7.97) and Miniature schnauzer (3.05, 95% confidence interval 1.67 to 5.57) had the highest odds of Cushing's syndrome. The Golden retriever (0.24, 95% confidence interval 0.06 to 0.98) and Labrador retriever (0.30, 95% confidence interval 0.17 to 0.54) were the most protected breeds. Increasing age, bodyweight greater than the breed‐sex mean and being insured also showed increased odds of Cushing's syndrome. Clinical Significance: As Cushing's syndrome is predominately diagnosed and managed in primary‐care practice, this study provides valuable new information of its epidemiology in this setting. Demographics reported are supportive of previous work and additional novel associations identified, such as the Border terrier, could enhance the index of suspicion for veterinarians.